Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(A=\frac{a}{ab+a+2}+\frac{b}{bc+b+1}+\frac{2c}{ac+2c+2}\)
\(=\frac{a}{ab+a+abc}+\frac{b}{bc+b+1}+\frac{abc^2}{ac+abc^2+abc}\)
\(=\frac{a}{a\left(bc+b+1\right)}+\frac{b}{bc+b+1}+\frac{abc^2}{ac\left(bc+b+1\right)}\)
\(=\frac{1}{bc+b+1}+\frac{b}{bc+b+1}+\frac{bc}{bc+b+1}\)
\(=\frac{bc+b+1}{bc+b+1}=1\)
cho mình xửa lại một chút nha:tính : A=\(\frac{a}{ab+a+2}+\frac{b}{bc+b+1}+\frac{2c}{ca+2c+2}\)
\(\frac{a}{ab+a+2}\)+ \(\frac{b}{bc+b+1}\)+ \(\frac{2c}{ac+2c+2}\)
= \(\frac{a}{ab+a+2}\)+ \(\frac{ab}{a\left(bc+b+1\right)}\)+ \(\frac{2abc}{ab\left(ac+2c+2\right)}\)
= \(\frac{a}{ab+a+2}\)+ \(\frac{ab}{abc+ab+a}\)+ \(\frac{2abc}{a^2bc+2abc+2ab}\)
= \(\frac{a}{ab+a+2}\)+ \(\frac{ab}{ab+a+2}\)+ \(\frac{2}{ab+a+2}\) (vì abc = 2 )
= \(\frac{ab+a+2}{ab+a+2}\)= 1
Sửa đề:
\(\frac{\left(a^2+b^2+c^2\right)\left(a+b+c\right)+\left(ab+bc+ca\right)\left(a+b+c\right)}{\left(a+b+c\right)^2-\left(ab+bc+ca\right)}\)
\(=\frac{\left(a^2+b^2+c^2+ab+bc+ca\right)\left(a+b+c\right)}{a^2+b^2+c^2+2ab+2bc+2ca-\left(ab+bc+ca\right)}\)
\(=\frac{\left(a^2+b^2+c^2+ab+bc+ca\right)\left(a+b+c\right)}{a^2+b^2+c^2+ab+bc+ca}\)
\(=a+b+c\left(a^2+b^2+c^2+ab+bc+ca\ne0\right)\)